Analisis Pengelolaan Persampahan di Kota Pangkajene Kabupaten Pangkep - Wona Grace Boro (Program Studi Teknik Sipil UKI Paulus-Makassar, 2021)
The increase in population greatly affects the measure of waste generation. The huge measure of waste is not supported by the number of waste management facilities and infrastructure, resulting in problems in waste management, such as transportation to final disposal of waste that is not properly accommodated, causing disease, dirty environment, reducing river carrying capacity and so on. This research was conducted to determine how waste management is in the city of Pangkajene and determine the infrastructure requirements for solid waste operational activities. This research is a quantitative descriptive study that gives an outline of how to oversee strong waste in the city of Pangkajene and the collection of quantitative data in the form of generation and composition of waste. According to the results of the research, the total amount of waste from the city of Pangkajene is 92.52 m3 / day. The average waste generated is 2.06m3 / day / person. From the calculation of solid waste infrastructure needs, it is obtained 900 units, 46 units of carts, 19 units of containers and 4 units of trucks every day. From the research results, it is concluded that the waste management system in Pangkajene city needs to be improved in terms of infrastructure and service levels in order to maximize solid waste operational activities.